A Review of Circular Economy Index from Many Perspective - IDAA Warmadewanthi; Arman Hakim Nasution; Alva Edy Tontowi; Mohamad Khoiru Rusydi; Gogor Arif Handiwibowo; Gita Widi Bhawika; Mochammad Andy Rizqy (IPTEK Journal of Proceedings Series, 2023)
The concept of a circular economy began to be launched worldwide due to the impact of increasing sustainability. The advancement of technology certainly makes it easier to implement a circular economy, especially in Industry 4.0. Several industries have implemented the concept of industry 4.0, but implementing a circular economy in the industry has yet to go well. The problem is that there needs to be a measurement of the circular level of the industry. This study aims as a literature study on determining the formulation of the circular economy index. The existence of gathering perspectives from various countries is expected to provide the application of the indicators that have the most influence on the measurement of the circular economy.